Transformation of Australian Community Pharmacies Into Good Clinical Practice Compliant Trial Pharmacies for HIV Pre-Exposure Prophylaxis - Lal, Luxi; Ryan, Kathleen; Liu, Iris Yi; Price, Brian; Lockwood, Timmy; Aguirre, Ivette; Slobodian, Peter; Lam, Ada; Vassan, Manoj; Lim, Kie; Silverii, John; Tesoriero, Joseph; et al. (Frontiers in Pharmacology, 2019)
Background In Australia, clinical trial drugs are conventionally dispensed through clinical trial pharmacies only, while community pharmacies dispense drugs approved by Australia’s regulatory body. A large HIV pre-exposure prophylaxis study aimed to deliver clinical trial drug through community pharmacies to improve convenience and mimic real world prescribing. This paper describes the process of making community trials compliant with good clinical practice and reports outcomes of delivering clinical trial drug through community pharmacies. Methods Eight community and four clinical trial pharmacies across three Australian states were approached to participate. A Good Clinical Practice checklist was generated and pharmacies underwent a number of changes to meet clinical trial pharmacy requirements prior to study opening. Changes were made to community pharmacies to make them compliant with good clinical trial practice including; staff training, structural changes and implementing monitoring of study drug and prescribing practices. Study drug was ordered through standard clinical trial processes and dispensed from study pharmacies by accredited pharmacists. Throughout the trial, record logs for training, prescriber signature and delegation, temperature, participant and drug accountability were maintained at each pharmacy. The study team monitored each log and delivered on-site training to correct protocol variations. Results Each pharmacy that was approached agreed to participate. All community pharmacies achieved good clinical practice compliance prior to dispensing study drug. Over the course of the study, 20,152 dispensations of study drug occurred, 83% of these occurred at community pharmacies. Only 2.0% of dispensations had an error, and errors were predominantly minor. On five occasions a pharmacist who was not accredited dispensed study drug. Conclusions Community based pharmacies can undergo training and modifications to achieve good clinical practice compliance and dispense clinical trial study drug. Community based pharmacies recorded few variations from study protocol. Community based pharmacies offer a useful alternative to clinical trial pharmacies to increase convenience for study participants and expanded use of these pharmacies should be considered for large clinical trials, including HIV prevention trials.